698. a) a2 + 2am + m²;
B) a2 + 4ab + 4b2;
6) x2 + 4x + 4;
r) b2 - 6b+9.​

uliamykytyn uliamykytyn    1   08.01.2021 14:00    1

Ответы
дарина25864 дарина25864  08.01.2021 14:10

a) Это формула квадратов (a+m)^2

b) (a+2b)^2

c) (x+2)^2

d) (b-3)^2

ПОКАЗАТЬ ОТВЕТЫ
kseniaksu1 kseniaksu1  08.01.2021 14:10

а) (\\a + m)^{2}

б) (\\a + 2b)^{2}

в) (\\x + 2)^{2}

г) (\\b - 3)^{2}

Объяснение:

а) a2 + 2am + m2 = (\\a + m)^{2}

б) a2 + 4ab + 4b2 = (\\a + 2b)^{2}

в) x2 + 4x + 4 = (\\x + 2)^{2}

г) b2 - 6b + 9 = (\\b - 3)^{2}

ПОКАЗАТЬ ОТВЕТЫ